Robust dc-link voltage tracking controller with variable control gain for permanent magnet synchronous generators - Kim, Seok Kyoon; Lee, Kyo Beum (Electronics (Switzerland), 2018)
This study develops a robust DC-link voltage tracking controller with variable control gain for permanent magnet synchronous generators. The first feature is to suggest an auto-tuning algorithm to drive the control gain to update the closed-loop cut-off frequency. The second one is to prove that the proposed controller incorporating auto-tuner and disturbance observer (DOB) coerces the closed-loop system to achieve the desired voltage tracking behavior, exponentially, with the steady-state rejection property. The control performance is demonstrated by emulating a wind-turbine power system using the powerSIM (PSIM) software.
Keywords: DC-link voltage control; Disturbance observer; PMSG; Variable control gain